2016
DOI: 10.1017/ipm.2015.69
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of co-facilitated information programmes on outcomes for service users and family members: the EOLAS programmes (paper 2)

Abstract: The EOLAS programmes offer a novel template for communication and information sharing in a way that embodies the principles of collaboration and offers users and families a meaningful opportunity to become involved in service design, delivery and evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…As the previous pilot evaluation of the EOLAS training (Higgins et al . ) and other literature illustrate (Coulthard et al . ), the traditional roles assumed by professionals and peer workers can sometimes be resistant to change, with both parties lapsing back into them, thereby maintaining power differentials in relation to status and input.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…As the previous pilot evaluation of the EOLAS training (Higgins et al . ) and other literature illustrate (Coulthard et al . ), the traditional roles assumed by professionals and peer workers can sometimes be resistant to change, with both parties lapsing back into them, thereby maintaining power differentials in relation to status and input.…”
Section: Discussionmentioning
confidence: 65%
“…In line with previous studies (Coulthard et al 2013;Thorneycroft & Dobel-Ober 2015), the present study demonstrates that a collaborative model in the production and delivery of services can work effectively, while at the same time, has the potential to advance the personal recovery of service user co-facilitators, as many reported experiencing the process as empowering. As the previous pilot evaluation of the EOLAS training (Higgins et al 2017b) and other literature illustrate (Coulthard et al 2013), the traditional roles assumed by professionals and peer workers can sometimes be resistant to change, with both parties lapsing back into them, thereby maintaining power differentials in relation to status and input. However, on the balance of the evidence provided in the present study, the training seems to have effectively surmounted these obstacles, with participants reporting that, over time, the power difference between professionals and users of services was dismantled, and genuine partnerships formed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to all non-pharmacological interventions in mental health care, the translation of psychoeducation's proven e cacy into routine mental health care has endured a protracted and challenging path. Despite the strength of the evidence-base in relation to psychoeducation [15][16][17][18][19][20], and its successful integration into policy recommendation and clinical guidelines [21][22][23][24], equitable access for many service users and family members has still not been achieved [25]. Alongside nascent research exploring the implementation determinants of one to one psychoeducation [26][27][28][29], a recent scoping review [30] reported some participant, practitioner, intervention, organisational and structural barriers and facilitators to group psychoeducation.…”
Section: Introductionmentioning
confidence: 99%